Nucleosome dynamics and remodeling - Widom, Jonathan (Henry Stewart Talks, 2007)
Chromatin composition, Nucleosome structure and function, Dynamic properties inherent to nucleosomes, Invasion of nucleosomes by gene regulatory proteins, DNA binding proteins and enzymes, ATP dependent remodeling factors, Nucleosome relocation